Role of Antimicrobial Peptides Expressed by Host Cells Upon Infection by Helicobacter pylori - Gopal, Ramamourthy; Jeong, Eunsil; Seo, Chang H.; Park, Yoonkyung (Protein and Peptide Letters, 2014)
Colonization of the stomach by Helicobacter pylori can result in such gastrointestinal illnesses as chronic gastritis, peptic ulcer and gastric cancer. Antimicrobial peptides (AMPs) are expressed in the stomach and play a key role in the innate immune responses to H. pylori in humans. During H. pylori infections, AMP expression mediated by NOD-1, NF-kB and/or ERK, functions to eradicate the bacteria, thereby preventing the gastritis and gastric cancer. This suggests that the use of synthetic AMPs could be one component of an effective therapeutic strategy to combat H. pylori. In addition, it appears that some peptides, and combinations of peptides, act synergistically with conventional drugs, thereby enhancing therapeutic efficacy. Our aim in this article was to review what is currently known about gastric AMP expression in response to H. pylori infection, and to briefly discuss the potential use of AMPs, either alone or in combination with conventional antibiotics, for the treatment of H. pylori infection.
Keywords: synergy effect